Rentabilidad financiera de la Empresa Disensa S.A del cantón Babahoyo de los períodos 2020 – 2021 - Marcial Cuadrado Rigail Francisco (2023)
This case study is based on the financial profitability of the Ecuadorian company Disensa, a leader in the market of marketing and distribution of construction materials, so the question of the company's financial profitability management is raised. Indeed, the objective of this case study is to identify the main variables resulting from the mismanagement of profits, using as a research technique an interview with the accountant of the organization, and obtain the data based on the financial statements provided by the organization to demonstrate the financial profitability it had in the periods 2020-2021. Using a vertical analysis of accounts to determine the participation of each account, and then a horizontal analysis to determine the changes in each account grouped by project, using a comparative analysis. A financial case is then developed to determine indicators such as liquidity, activity, indebtedness and profitability, which can give a realistic picture of the company's economic and financial situation. In this way, problems are identified and addressed in such a way that new ideas and decisions are chosen to achieve a good organizational synergy. Finally, improvement programs will be developed in the sales area in order to implement transforming actions in the further development of the economic and financial activities